CHARACTERISTIC PHYSICOCHEMICAL OF BAMBOO-BASED ACTIVATED CARBON FOR COAL RUN-OFF WATER TREATMENT USED AT PT.BUKIT ASAM SLUDGE SETTLEMENT POND - Oktaf Rina; Anggi Saputra; Yatim R. Widodo; Syahdilla Anggiva Akhni Rarasati; Ajis Purnomo; Aang Haryadi (International Journal of Social Science, 2023)
The aim of this research were investigated bamboo-based activated charcoal (ABT)characteristics using Scanning Electron Microscopy (SEM) and Fourier Transform Infrared (FTIR). ABT has been successfully synthesized through physico-chemical activation at 700°C with H3PO4 10% solution as activator. The resulted were porous surface structure of bamboo charcoal causes an absorption interaction of pollutants (cations, anions, and suspended solids/TSS) in wastewater. Bamboo charcoal has different physical characteristics from charcoal from other types of raw materials because the structure with lignin composition is different from charcoal from other wood. The spectral patterns of AB and ABT are similar but differ in intensity. The functional groups detected in the two materials are the same, but there are differences in the absorption intensity where the ABT is relatively lower, especially in the hydroxyl functional groups at around 3400 and 1600 cm-1. This decrease in intensity is due to the dehydration process that occurs during both physical and chemical activation processes so that the hydroxyl groups come out of the bamboo charcoal structure